Strategi Pengelolaan Danau Sepunjung Desa Rantau Baru Kecamatan Pangkalan Kerinci Kabupaten Pelalawan - Desti Zarli Mandari; Thamrin Thamrin; Ridwan Manda Putra (Pelantar Press, 2023)
Sepunjung Lake is a natural lake located in Rantau Baru Village which is a fishing area for the Rantau Baru community, especially for female fishermen who are widows. However, there is currently a decline in fish catches in Lake Sepunjung. This study was conducted to determine the existing condition of the lake, influencing factors, and formulate a management strategy for Lake Sepunjung. The methods used were field observations, interviews and literature studies. The analysis used included analysis for water quality, descriptive analysis and SWOT analysis. The results of this study showed that the ecological condition of Lake Sepunjung is still in the good category, social conditions are good by maintaining local wisdom and minimal conflict, while economic conditions are still relatively low due to the low income of Rantau Baru fishermen. The resulting strategy is the S-O strategy, supporting all strengths and utilizing existing opportunities, by: (1) Establishing Village Regulations in an effort to protect the biophysical quality of lake waters, vegetation cover around the lake, and biodiversity in Lake Sepunjung; (2) Management of ecotourism based on local wisdom; and (3) Development of freshwater fisheries potential.